Análise regional dos resultados do Saresp: uma abordagem com modelos hierárquicos - Bassetto, Camila Fernanda [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (UNESP), Faculdade de Ciências, campus de Bauru., 2021)
This study investigates school-internal and school-external factors that impact on student scholastic performance. Therefore, we used the math performance in SARESP of students in the 3rd grade of high school enrolled in public schools of São Paulo state and their parents' answers to questionnaires administered by participating schools. The schools were classified into regions according to the Board of Education to which they belong, thus enabling a spacial analysis of students’ math performance. Multilevel models were proposed, and the parameters estimates were obtained using RStudio software. Results show that the schooling of parents, family income and the fact that students do their homework positively impact on a student's mathematics performance in SARESP. On the other hand, while the inadequate number of teachers affects student results, more experienced school managers have a positive effect on the performance in mathematics in SARESP.

O presente estudo investiga os fatores internos e externos à escola, que impactam o desempenho escolar dos alunos. Para tanto, foram utilizadas as notas em matemática, alcançadas no SARESP, pelos alunos da 3ª série do Ensino Médio das escolas públicas estaduais de São Paulo e as respostas dos questionários aplicados aos pais e às escolas participantes. As escolas foram classificadas em regiões conforme a Diretoria de Ensino a qual pertencem, possibilitando o desenvolvimento de uma análise espacial do desempenho em matemática. Modelos multiníveis foram propostos e as estimativas para os parâmetros foram obtidas via software RStudio. Os resultados mostram que a escolaridade dos pais, a renda familiar e o motivo de o aluno fazer o dever de casa, impactam positivamente o desempenho em matemática. Por outro lado, enquanto a falta de professor prejudica o resultado do aluno, gestores mais experientes têm efeito positivo sobre o desempenho em matemática no SARESP.
The local analysis of Saresp results: an approach with hierarchical models
Keywords: Evaluation of school performance; Mathematics proficiency; Public school; High school; SARESP; Avaliação do rendimento escolar; Proficiência em matemática; Escola pública; SARESP